Kinetic modeling of hyperpolarized 13C pyruvate metabolism in tumors using a measured arterial input function. Issue 4 (20th November 2012) - Kazan, S. M.; Reynolds, S.; Kennerley, A.; Wholey, E.; Bluff, J. E.; Berwick, J.; Cunningham, V. J.; Paley, M. N.; Tozer, G. M.
<x xml:space="preserve">Abstract</x> Mathematical models are required to estimate kinetic parameters of [1‐13C] pyruvate‐lactate interconversion from magnetic resonance spectroscopy data. One‐ or two‐way exchange models utilizing a hypothetical approximation to the true arterial input function (AIF), (e.g. an ideal 'box‐car' function) have been used previously. We present a method for direct measurement of the AIF in the rat. The hyperpolarized [1‐13C] pyruvate signal was measured in arterial blood as it was continuously withdrawn through a small chamber. The measured signal was corrected for T1 relaxation of pyruvate, RF pulses and dispersion of blood in the chamber to allow for the estimation of the direct AIF. Using direct AIF, rather than the commonly used box‐car AIF, provided realistic estimates of the rate constant of conversion of pyruvate to lactate, kpl, the rate constant of conversion of lactate to pyruvate klp, the clearance rate constant of pyruvate from blood to tissue, Kip, and the relaxation rate of lactate T1la. Since no lactate signal was present in blood, it was possible to use a simple precursor‐product relationship, with the tumor tissue pyruvate time‐course as the input for the lactate time‐course. This provided a robust estimate of kpl, similar to that obtained using a directly measured AIF. Magn Reson Med, 70:943–953, 2013. © 2012 Wiley Periodicals, Inc.